Finding 'pockets of possibility' for anti‐racism in a curriculum for student teachers: From absence to action. Issue 1 (26th September 2022) - Smith, Heather; Lander, Vini
Abstract: Many institutions have found the strength to name racism and seek space for curriculum and other systemic changes. We argue this is happening against a backdrop of curriculum, regulatory and policy changes in education, and particularly initial teacher education and training (ITE/T), which are de‐racialised. We propose that a 'pocket of possibility' lies within such divergences, and present research leading to the creation of an anti‐racism framework for ITE/T to support action against this emergent landscape. The paper documents each aspect of the research and snapshots of the findings of a global literature review of anti‐racism in initial teacher education, which demonstrated the need for an embedded approach to anti‐racism, informed by critical understandings of whiteness and racism. We share some of the complexities, obstacles, and effective anti‐racism practices revealed in the review. The findings of the review led to the creation and analysis of a survey for ITE/T providers in England, which provided encouraging evidence of useful practice alongside needs of the profession. We conclude with a statement of intent and hope to maximise of the minimum entitlement of the Core Content Framework (CCF) by a purposeful undoing of the perpetual de‐racialisation of education.